A Fourty-One Year Review of Deaths from Motor Accidents in Lagos State, Nigeria (1970-2010) - Atubi, Augustus .O. (Richtmann Publishing, 2012)
Using mostly secondary data on vehicular accidents obtained from the Nigeria Police Force and Federal Road SafetyCommission, the study examined a thirty-two year review of deaths from road traffic accidents (1970-2010) in Lagos State. The reporteddeaths from road traffic accidents in the 20 Local Government Areas of Lagos State were compared using the Analysis of Variance(ANOVA). The result showed that for the two factors, Local Government Areas and years, the F-calculated of 18.32 and 7.43respectively were higher than the F-tabular of 1.64 and 1.32 respectively at 0.05 level of significance. It then implies that the means foreach of the factors, reported deaths from road traffic accidents across the 20 Local Government Areas of Lagos State and acrossdifferent years were significantly different. The result of the multiple regression analysis was 0.32. This implies that the proportion ofvariation in the dependent variable (i.e. deaths from road traffic accidents) explained by the independent variables (i.e. length of roads,presence of road safety and population) was 32%. Based on the findings, recommendations were proffered on how to reduce thephenomenon of deaths from traffic accidents in Lagos State.